2009
DOI: 10.1108/02640470911004075
|View full text |Cite
|
Sign up to set email alerts
|

Application of information technologies in academic libraries

Abstract: PurposeThe main purpose of this investigation is to define the status of the application of information technology in academic libraries located in Kerman, the center and largest city of Kerman Province, Iran, and to understand the problems and difficulties in using information technology in these libraries.Design/methodology/approachThe survey has covered 17 libraries belonging to Shahid Bahonar University, Kerman Medical University and Islamic Azad University. Two kinds of questionnaires were distributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The findings of the research showed that the managers of hospital libraries at all the three universities have accepted as well as acknowledged the role of IT skills in providing better services to users. These points are also reinforced by the findings of the research carried out by Mirjud (1992), Koivunen (2009), and Mohsenzadeh and Isfandyari‐Moghaddam (2009). The library managers of the three universities acknowledged the need for the improvement of their skill in different areas of IT.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The findings of the research showed that the managers of hospital libraries at all the three universities have accepted as well as acknowledged the role of IT skills in providing better services to users. These points are also reinforced by the findings of the research carried out by Mirjud (1992), Koivunen (2009), and Mohsenzadeh and Isfandyari‐Moghaddam (2009). The library managers of the three universities acknowledged the need for the improvement of their skill in different areas of IT.…”
Section: Discussionmentioning
confidence: 84%
“…A good number of the library users were not satisfied with the application of ICT in their libraries and indicated “inadequate ICT infrastructure” as their major reason for dissatisfaction. Mohsenzadeh and Isfandyari‐Moghaddam (2009) performed a study to define the status of the application of IT in academic libraries in Kerman, Iran. Results showed that the level of application of IT in Kerman academic libraries was acceptable, but efforts should be made to improve their status to match with the ever‐increasing demand for better library services at universities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies, such as those by Travica (1999), Chowdhury and Chowdhury (2003), Mohsenzadeh and Isfandyari-Moghaddam (2009), and Isfandyari-Moghaddam ( 2009) report that the emergence of the digital environment has led to changing librarians' traditional skills as well as functions. It is important for academic librarians to learn new technologies including DLs to continue their activities as real information professionals in the twenty-first century.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the use of information technology in libraries, Mohsenzadeh and Isfandyari-Moghaddam (2009) indicate that academic and research libraries introduced information technologies “to speed up their daily activities and reduce their operation costs”. Bazillion (2001), however, added another dimension by positing that [these] technological tools “made a strong impact on learning” and “a positive impact on academic achievement”.…”
Section: Literature Reviewmentioning
confidence: 99%